Appearance of spore coat protein in the cell extracts of Bacillus subtilis asporogenic mutants. - Uchida, A (1976)
By use of the antigen-antibody techniques we have studied whether asporogenic mutants of Bacillus subtilis can synthesize the spore coat protein. Antibody specific to spore coat protein was prepared and used to demonstrate that the spore coat protein was synthesized at the early stage of sporulation. We report here that asporogenic mutants synthesize the spore coat protein.